Two Rivers: The Politics of Wild Salmon, Indigenous Rights and Natural Resource Management - Gro Ween; Benedict Colombi (Sustainability, 2013)
This paper compares two rivers, Tana River in Northern Norway and Columbia River on the northwest coast of the United States of America. Both rivers host indigenous populations, the Sámi and the Nez Perce, whose cultural and material existence depends upon salmon. Because these people live indigenously within highly industrial, postcolonial societies, their lives have been part of larger economic, political and legal structures for substantial periods of time. In these rivers, peoples have been, and are currently dealing with the possibility of salmon extinction. This article is concerned with how such a crisis has been interpreted and acted upon within two nation’s natural-resource management regimes. We observe how the threat of extinction has initiated commotion where nature, economies, legal instruments, politics and science have come into play, in ways that reveal differences in the Norwegian and American constellations of interests and powers, manifested as differences in natural resource management regimes’ hierarchies of positions. The outcome is the protection of different entities, which could be labeled cultural and biological sustainability. In the Columbia River, cultural sustainability was promoted while in the Tana, biological sustainability became prioritized. By way of our comparison we ask if the protection of one kind of sustainability has to be to the detriment of the other.